2023
DOI: 10.1017/jfm.2022.1084
|View full text |Cite
|
Sign up to set email alerts
|

Disk wakes in nonlinear stratification

Abstract: Nonlinearity of density stratification modulates buoyancy effects. We report results from a body-inclusive large eddy simulation of a wake in nonlinear stratification, specifically for a circular disk at diameter-based Reynolds number ( ${\it Re} $ ) of $5000$ . Five density profiles are considered; the benchmark has linear stratification and the other four have hyperbolic tangent profiles of the same thickness to model a pycnocline. The disk moves inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the influence of the angle of attack and surface properties (roughness, porosity) on the development of these structures could be explored. Also, it is worth investigating how density stratification (Nidhan, Schmidt & Sarkar 2022;Gola et al 2023), often found in the natural environment, affects the lift-up mechanism and formation of streaks in turbulent disk wakes. Finally, a direct comparison of the characteristics of streaks in wakes, such as length scales, intermittency and life cycle, with those in other turbulent flows, such as channel flows and jets, can inform about potentially universal behaviour of streaks in turbulent flows.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the influence of the angle of attack and surface properties (roughness, porosity) on the development of these structures could be explored. Also, it is worth investigating how density stratification (Nidhan, Schmidt & Sarkar 2022;Gola et al 2023), often found in the natural environment, affects the lift-up mechanism and formation of streaks in turbulent disk wakes. Finally, a direct comparison of the characteristics of streaks in wakes, such as length scales, intermittency and life cycle, with those in other turbulent flows, such as channel flows and jets, can inform about potentially universal behaviour of streaks in turbulent flows.…”
Section: Discussionmentioning
confidence: 99%